Durability study of concrete with partial replacement of cement with fly ash and eggshell powder - Ding, Yong Jie (2018)
It is well known that construction industry has accounted for 7% of total carbon dioxide emission globally. During the production of concrete, it needs a lot of raw material and it is also one of the source for greenhouse gas emission, creating global warming and climate change. Therefore, it is necessary to reduce the cement content in concrete by using green and reusable waste materials. In this study, fly ash and eggshell powder was used as partial replacement of Ordinary Portland Cement. Fly ash are by-products from power plant and eggshell is waste from hatcheries or food industries. These waste are being disposed in landfill and cause environmental pollution. The properties of these materials are suitable to be use to substitute limestone. Four different percentages of cement replacement by fly ash and eggshell powder with a water to cement ratio of 0.4 were used for this research. Mechanical and durability properties of the produced concretes were studied. The investigations focused on compressive strength, water absorption, water penetration, acid attack and sulphate attack test at different percentages of replacement. From the investigation, all the concrete cubes have achieved the desired strength of 30MPa for 28days curing. For the mixes with fly ash and eggshell powder, 30FA 5ESP has the highest strength of 48.58MPa. The rate of water absorption and water penetration reduced with the increase of cement replacement by FA and ESP. However, when the replacement exceed 40%, the percentage of water absorption and depth of water penetration increase. The mass loss percentage and strength loss percentage due to acid attack was minimum for 30FA 5ESP mix and maximum for normal concrete. The strength loss percentage due to sulphate attack was minimum for 30FA 5ESP mix. The further replacement will increase the percentage of strength loss and the strength loss is higher than the normal concrete. The results obtained indicate that a total of 35% replacement is the most optimum replacement percentage. The concrete strength dropped and durability became lower when further increase the percentage of replacement. Thus, it is possible to contribute to construction sustainability and build more durable structures by substituting the cement content in concrete with fly ash and eggshell powder.